Biomimetic strategies for engineering composite tissues. (August 2016) - Lee, Nancy; Robinson, Jennifer; Lu, Helen
Graphical abstract: Highlights: The formation of composite tissues reflective of native tissue structure and function represents a frontier challenge. Stratified and gradient-scaffolds coupled with cells and growth factors enable multi-tissue formation. Strategic biomimicry is applied to scaffold design to recapitulate key tissue properties and expedite translation. Abstract : The formation of multiple tissue types and their integration into composite tissue units presents a frontier challenge in regenerative engineering. Tissue–tissue synchrony is crucial in providing structural support for internal organs and enabling daily activities. This review highlights the state-of-the-art in composite tissue scaffold design, and explores how biomimicry can be strategically applied to avoid over-engineering the scaffold. Given the complexity of biological tissues, determining the most relevant parameters for recapitulating native structure–function relationships through strategic biomimicry will reduce the burden for clinical translation. It is anticipated that these exciting efforts in composite tissue engineering will enable integrative and functional repair of common soft tissue injuries and lay the foundation for total joint or limb regeneration.